A Week Is a Long Time in Politics: The Health Implications of Jeremy Corbyn's UK Labour Party Leadership Victory. (January 2016) - Scott-Samuel, Alex; Bambra, Clare
For more than 30 years, socialism within the UK Labour Party – which was in government from 1997 to 2010 and is currently the main UK parliamentary opposition – has been in decline. Despite its origins as a party of and for the working class, Labour has become at best a social democratic party with strong neoliberal leanings. However, in the recent leadership election that followed Labour's general election defeat in May 2015, the socialist Jeremy Corbyn confounded all expectations by winning Labour's leadership with a substantial majority. We describe the political context of Corbyn's controversial victory and discuss its potential short- and medium-term impact on England's troubled National Health Service and on the public health.